The Role of Transformational Leadership and Work-Life Balance In Improving the Performance of ASN Employees Through Job Satisfaction - Suherdi, Heri; Mukhlis, Ahmad; Suadma, Udin (Jurnal Economic Resource, 2025)
In the globalization era, civil servant (ASN) performance is a critical determinant of public sector success. This study investigates the impact of transformational leadership and work-life balance on employee performance, with job satisfaction serving as a mediating variable. Using a quantitative design, data were collected via a five-point Likert scale questionnaire from 73 civil servants at the Department of Public Works and Spatial Planning (PUPR) in Cilegon City. The analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. Results indicate that both work-life balance and job satisfaction significantly enhance employee performance. Transformational leadership positively influences job satisfaction but shows no direct effect on performance. Moreover, job satisfaction mediates the relationship between work-life balance and performance, but not between transformational leadership and performance. These findings emphasize the importance of implementing effective work-life balance policies and fostering job satisfaction to improve performance outcomes. Public sector organizations should prioritize supportive leadership practices, balanced workloads, and employee well-being initiatives to sustain high performance levels